Modes of Delivery in Concurrent Nicotine and Cannabis Use ("Co-Use") among Youth: Findings from the International Tobacco Control (Itc) Survey. Issue 3 (July 2021) - Smith, Danielle M.; Miller, Connor; O'Connor, Richard J.; Kozlowski, Lynn T.; Wadsworth, Elle; Fix, Brian V.; Collins, R. Lorraine; Wei, Binnian; Goniewicz, Maciej L.; Hyland, Andrew J.; Hammond, David
Background: Cannabis use is more common among nicotine users than non-users. This study characterized concurrent use of nicotine and cannabis ("co-use") among 12, 064 youth aged 16–19 years residing in Canada, the United States, and England in 2017. Methods: Data were from the ITC Youth Tobacco & Vaping Survey (Wave 1). Seven modes of cannabis delivery (MOD) were characterized by country of residence and past 30-day use of combusted tobacco and electronic cigarettes. Weighted multivariable regression models were fitted to assess the correlates of co-use and each cannabis MOD. Results: Seventy percent of cannabis users reported nicotine use. Co-users exhibited behavioral and demographic differences compared to exclusive users of either substance. "Smoking cannabis without tobacco" was the most popular form of use (78%). Use of nicotine-containing e-cigarettes was associated with "using an e-cigarette to vape cannabis oil/liquid" (aOR: 4.96, 95%CI: 2.23–11.06). Combustible tobacco use was associated with "smoking cannabis with tobacco in a joint/blunt" (aOR: 2.93, 95%CI: 1.89–4.56). Country-level differences were detected. Conclusions: Nicotine use is substantial among cannabis users, and associations exist between modes of delivery for both drugs. Results underscore the importance of studying cannabis and nicotine use concurrently, and the need to address the use of both substances in developing interventions for youth users.